2021
DOI: 10.3390/app11125401
|View full text |Cite
|
Sign up to set email alerts
|

Development of Modular Bio-Inspired Autonomous Underwater Vehicle for Close Subsea Asset Inspection

Abstract: To reduce human risk and maintenance costs, Autonomous Underwater Vehicles (AUVs) are involved in subsea inspections and measurements for a wide range of marine industries such as offshore wind farms and other underwater infrastructure. Most of these inspections may require levels of manoeuvrability similar to what can be achieved by tethered vehicles, called Remotely Operated Vehicles (ROVs). To extend AUV intervention time and perform closer inspection in constrained spaces, AUVs need to be more efficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It was also shown that similar kinematics and propulsive capability of the real fish may be replicated via purely passive structural deformations when using a bionic body stiffness profile (Luo et al 2020). The RoboFish device was demonstrated in lake trails and shown to be functional in terms of water-tightness, propulsion, body control and communication using acoustics, with visual localisation and mapping capability (Gorma et al 2021).…”
Section: F2 Use Of Autonomous Systems For Inspectionmentioning
confidence: 98%
“…It was also shown that similar kinematics and propulsive capability of the real fish may be replicated via purely passive structural deformations when using a bionic body stiffness profile (Luo et al 2020). The RoboFish device was demonstrated in lake trails and shown to be functional in terms of water-tightness, propulsion, body control and communication using acoustics, with visual localisation and mapping capability (Gorma et al 2021).…”
Section: F2 Use Of Autonomous Systems For Inspectionmentioning
confidence: 98%
“…The constant wear and corrosion of infrastructure in harsh underwater environments drives up maintenance costs, and these tasks are currently carried out primarily with remotely operated vehicles (ROVs), which often require tethered and human operators, or with autonomous underwater vehicles (AUVs), which are limited in their accessibility and maneuverability. In order to reduce the risk and cost of manual maintenance, underwater bionic robots can be used to check and measure underwater cables, offshore wind farms, electric fields and other underwater infrastructure (Gorma et al, 2021). Therefore, FDPSO is quite suitable for the development of China's offshore oil and gas fields.…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned vehicles, encompassing unmanned surface vehicles and unmanned underwater vehicles, have received increasing attention over the past several decades. They have found widespread applications in complex, hazardous, and even extreme aquatic environments, such as search and rescue [ 1 ], environmental survey and monitoring [ 2 ], underwater infrastructure inspection and maintenance [ 3 ], sea exploration [ 4 ], and oceanographic observation [ 5 ]. Although traditional propulsion technologies are well-developed and easy-to-use, underwater robots and vehicles powered by rotating propellers are often bulky, noisy, and not sufficiently maneuverable, which hardly meets the ambitious requirements of high maneuverability and stealthiness in marine areas.…”
Section: Introductionmentioning
confidence: 99%